Développer et réduire
H= ( - 2x -2) 3x - 7x (3x-1)
J= 3x(2x-5) -(-4x au carré - 3)
K=(2x+7)(8+3x) -5x au carré - 15
L=(-5x+3)(-3 -4x) -6x (-2x-5)
M=(5-3x)4x + (-2x-5) (-3x-7)
N=(-3x+4) (-5+6x) + (7x au carré + 15x-16)
P= -3x (-5-2x +7x au carré) - (8x au carré -10x -3)

2

Réponses

2014-05-28T23:20:40+02:00
H=(-2x-2)3x - 7x(3x-1)=-6x au carré-6x - 21x au carré +7x=x-27x au carré
J=3x(2x+5)-(-4x aucarré -3)=6x au carré + 15x + 4x au carré + 3 =10xau carré + 15 + 3
k=(2x+7)(8+3x)-5x au carré-15=16x+6x au carré+56+21x-5xau carré-15 = x au carré + 37x+41
L=(-5x+3)(-3-4x)-6x(-2x-5)=15x+20x au carré -12x+12x au carré + 30x=32x au carré+33x-9
........
2014-05-28T23:22:51+02:00
H= (-2x -2) 3x -7x (3x-1)
= -6x² -6x -21x² +7x
= -27x² +x

J= 3x (2x -5) - (-4x²-3)
= 6x² -15x +4x² +3
= 10x² -15x +3

K= (2x+7)(8+3x) -5x² -15
= 16x +6x² +56 +21x -5x² -15
= x² +37x +41

L= (-5x +3)(-3-4x)-6x (-2x -5)
= +15x +20x² -9 -12x +12x² +30x
= 33x +32x² -9

M= (5-3x) 4x+(-2x-5)(-3x-7)
= 20x -12x² +6x² +14x +15x +35
49x -6x²  +35

N= (-3x+4)(-5+6x)+(7x²+15x-16)
= +15x -18x² -20 +24x +7x² +15x -16
= 54x -11x² -36

P= -3x (-5 -2x +7x²) - (8x² -10x -3)
= -3x -5 -2x +7x² -8x² -10x -3
= -15x -8 -x²